Ruptured Ectopic Pregnancy with Contralateral Ovarian Serous Cyst Adenoma Torsion: Laparoscopic Management of Double Trouble - Deepa Ganesh; Anirudh Rajkumar; J. S. Rajkumar; Venkatesan Guru (Hindawi Limited, 2016)
Adnexal torsion is responsible for 2.7% of all gynecological emergencies. Ectopic pregnancy is relatively common, occurring in 2% of all pregnancies. We report the second case of ruptured right tubal ectopic gestation with torsion of serous cystadenoma of left ovary. This was diagnosed after emergency laparoscopy done for acute abdomen. Right salpingectomy and left ovarian detorsion followed by cystectomy were done laparoscopically.